Ethnolinguistic Encoding of Cosmology and Social Hierarchy in Sundanese Life-Cycle Ritual Discourse - Hadiati, Diah Nur; Nursafitri, Restuti; Al-Dhamari, Gamal Abdo Nasser; Selvarajan, Saraswathy (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to describe and analyze the linguistic forms, ritual lexicons, and cultural meanings embedded in Sundanese life-cycle ceremonies using an ethnolinguistic approach to reveal how language reflects cultural concepts, belief systems, and social structures. Methodology: This study employed a qualitative descriptive design with an ethnolinguistic framework. Data were collected through participant observation, semi-structured interviews, documentation study, audio recording, and field notes. Purposive sampling was applied. Data were analyzed using lexical classification, semantic analysis, pragmatic analysis, cultural interpretation, and triangulation techniques. Main Findings: The findings reveal that Sundanese life-cycle rituals contain structured ritual lexicons across pregnancy, birth, childhood, marriage, and death phases. These lexicons function as symbolic-cultural representations encoding cosmology, agrarian metaphors, religious syncretism, and social hierarchy through undak usuk basa. Ritual language operates as a semiotic system preserving collective memory and worldview. Novelty/Originality of this study: This study offers a comprehensive ethnolinguistic mapping of Sundanese life-cycle ritual lexicons by integrating semantic, pragmatic, and cultural analyses in one framework. It advances knowledge by demonstrating how ritual language systematically encodes cosmology, social hierarchy, and ecological cognition within contemporary cultural contexts.